Mechanical and water absorption properties of sawdust—low density polyethylene nanocomposite. Issue 2 (22nd May 2012) - Esnaashari, Catherine; Khorasani, Saied Nouri; Entezam, Mehdi; Khalili, Shahla
Abstract In this research, effect of nanoclay (Cloisite10A), coupling agent (MAPE), spruce sawdust and electron beam irradiation dose on mechanical and water absorption properties of sawdust‐low density polyethylene nanocomposite are investigated. Design of the experiments (DOE) is performed by the statistical Taguchi method. The XRD analysis depicts partially intercalated/exfoliated nanocomposites. The findings reveal that increasing cloisite10A concentration from 2.5 to 7.5 wt % has improved the tensile and bending strengths and modulus also water diffusion coefficient is reduced. Increase the sawdust content from 40 to 60 wt % not only markedly increases the tensile and flexural properties but also increases water diffusion coefficient and reduces toughness significantly. Electron beam irradiation dose of 60 kGy improves the tensile and flexural properties and decreases water diffusion coefficient. The SEM micrographs confirm a suitable coherence between lignocelluloses filler phase and low density polyethylene matrix. © 2012 Wiley Periodicals, Inc. J. Appl. Polym. Sci., 2013